KECENDERUNGAN KEPUASAN KERJA SEBAGAI TRIGGER TURNOVER - Raditya Adi Saputra (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
The purpose of this study are: (1) To determine the effect of job satisfaction on turnover intention; (2) To determine the effect of work stress on turnover intention; (3) To determine the effect of compensation on turnover intention; (4) To determine the effect of organizational climate on turnover intention; and (5) To determine the stress of work, compensation, organizational climate and job satisfaction effect on turnover intention. The population in this study are employees of the Cooperative KOKAPURA AVIA totaling 180 people, while employees who have worked more than three years as many as 128 people. Samples were taken 97 people. The technique of collecting data using questionnaires. The analysis used is multiple regression analysis and path analysis using PLS 3.0 Smart program. Based on the results of the study concluded that: (1) Job satisfaction significantly influence employee turnover intention; (2) Work stress significantly influence employee turnover intention; (3) Compensation incentives significantly influence employee turnoverÂ Â  intention; (4) organizational climate significantly influence employee turnover intention; and (5) Work stress, incentive compensation, organizational climate and job satisfaction simultaneously significantly influence employee turnover intention.Keyword: work stress, incentive compensation, organizational climate, job satisfaction, turnover intention